2009
DOI: 10.1055/s-0029-1239490
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Placental Abruption in Underweight Women

Abstract: We sought to determine if there is a relationship between prepregnancy underweight status and placental abruption. We utilized the Missouri maternally linked cohort data files covering the period 1989 through 1997. We estimated the association between prepregnancy underweight subtypes and placental abruption using adjusted odds ratios. Subanalyses were performed to determine whether the amount of weight gained during pregnancy could modify the association. A total of 439,235 singleton pregnancies with 3696 abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Maternal underweight was also linked to excess hospital costs, although this was mainly due to higher costs associated with baby admissions. This makes intuitive sense, as babies born to women who are underweight are at increased risk of adverse perinatal outcomes, including prematurity, low birth weight and small for gestational age . ICU/SCN costs contributed to most of the differential, suggesting that the excess cost reflects the increased resources required to treat ‘at‐risk’ babies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal underweight was also linked to excess hospital costs, although this was mainly due to higher costs associated with baby admissions. This makes intuitive sense, as babies born to women who are underweight are at increased risk of adverse perinatal outcomes, including prematurity, low birth weight and small for gestational age . ICU/SCN costs contributed to most of the differential, suggesting that the excess cost reflects the increased resources required to treat ‘at‐risk’ babies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have consistently shown overweight and obesity to be associated with complications such as gestational diabetes, hypertension, macrosomia and still birth . Women who are underweight are also at increased risk of adverse outcomes, including preterm birth, placental abruption, miscarriage, low birth weight and small for gestational age …”
Section: Introductionmentioning
confidence: 99%
“…In females, low BMI during childhood and adolescence increases women's risk for later endometriosis [12], preterm birth [13], low infant birth weight [14] and increased risk for placental abruption [15]. Infants born to mothers with low BMI have an increased risk for atrial septal defect, genital abnormalities including hypospadias [16].…”
Section: Introductionmentioning
confidence: 99%
“…[15] Deutsch et al showed in their study conducted in 2010 that placental abruption risk was increasing in slim women (OR=1.4; 95% CI: 1.3-1.5). [16] Salihu et al indi- cated that placental abruption risk was increasing if weekly weight gaining of pregnant women with normal weight is ≤0.22 kg/week (aOR=1.8; 95% CI: 1.5-2.2), and the risk was decreasing in obese women. [17] In our study, mean BMI was found as 29.3±4.8 in the group with confirmed placental abruption diagnosis, but there was no significant difference when groups were compared.…”
Section: Discussionmentioning
confidence: 99%